Characterization and classification of volatiles from different breeds of eggs by SPME-GC–MS and chemometrics. (February 2019) - Xiang, Xiao-le; Jin, Guo-feng; Gouda, Mostafa; Jin, Yong-guo; Ma, Mei-hu
Abstract: Volatiles of shell eggs were identified by SPME-GC–MS to characterize and discriminate white Leghorn (W), Hy-line brown (H) and Jing fen (J) hatching eggs with comparison, principal components (PC), partial least squares (PLS), random forest classification (RFC) and canonical discriminant (CD) analyses. DVB/CAR/PDMS fiber and extraction 60 min were suited to analyze the volatiles emitted from eggs. A total of 17 or 18 volatile compounds were identified in raw shell hatching eggs, namely, nonanal, decanal and 6-methly-5-hepten-2-one were the main volatile components with contributions that over 70%. The composition and/or profile of volatile compounds from W and H eggs were much more similar than J eggs. Hexanal, decanal, 6-methly-5-hepten-2-one, heptanal, etc. have greatly contributed to the distinction of W, H and J eggs in sparse ( S )-PLS and orthogonal (O)-PLS models. The accuracy of RFC and CD model were 100%, 100% (initial) and 83.3% (cross-validation), respectively. Heptanal, 6-methly-5-hepten-2-one, octanal, etc. were contributed positively to the classification of W, H, J eggs in RFC, especially for heptanal. Graphical abstract: Unlabelled Image Highlights: DVB/CAR/PDMS fiber and extraction 60 min were suited to analyze the volatiles of raw shell hatching eggs by SPME-GC-MS. Nonanal, decanal, 6-methly-5-hepten-2-one, levomethol, cedrene, etc. 17/18 VOCs were found in raw shell hatching eggs. Hexanal, decanal, 6-methly-5-hepten-2-one, heptanal, cedrene showed high positive influence on the variation of W, H, J eggs. The accuracy of classification among W, H, J eggs in RFC, CD models were 100%, and in cross validation of CD model was 83.3%. Heptanal may be used as an indicator to discriminate eggs with different breeds.